Effect of Zinc and Magnesium on Orange Fleshed Sweet Potato in Alfisols of Odisha, India - Laxminarayana, K; K, Susan John (JOURNAL OF ROOT CROPS, 2015)
The effect of application of magnesium (Mg) and zinc (Zn) individually and in combination on yield, proximate composition and nutrient uptake of orange fleshed sweet potato was studied in an acidic Alfisol of Odisha, India by conducting field experiments for two kharif (rainy) seasons during 2009-10 and 2010-11. The results revealed that significantly highest mean tuber yield (11.9 t ha-1) and vine yield (18.1 t ha-1) was recorded due to application of 20 and 30 kg ha-1 of ZnSO4 and MgSO4, respectively. The mean yield response was pronounced to be 12, 19 and 10 % due to application of 10, 20, and 30 kg ZnSO4 ha-1 over control, while it was 7, 11 and 8 % with respect to 15, 30, and 45 kg MgSO4 ha-1. Highest mean starch content (22.4%), total sugars (3.61%) and dry matter (29.4%) was observed due to application of 20 kg ha-1 ZnSO4. Combined application of 20 and 30 kg ha-1 of ZnSO4 and MgSO4 recorded significantly highest total uptake of N and P (67.4 and 24.7 kg ha-1, respectively), however, the total uptake of K was highest (93.1 kg ha-1) due to 10 and 45 kg ha-1 of ZnSO4 and MgSO4. Addition of Zn and Mg resulted in significant improvement of soil properties. The results emphasized that application of 20 and 30 kg ha-1 of ZnSO4 and MgSO4, respectively along with the optimum doses of NPK produces highest and sustainable crop yields with good quality tubers and maintains the soil fertility.